Heterogeneity in the Attachment and Uptake Mechanisms of the Legionnaires’ Disease Bacterium, Legionella pneumophila, by Protozoan Hosts - Harb, Omar S. (American Society for Microbiology, 1998)
Invasion and intracellular replication of Legionella pneumophila within protozoa in the environment plays a major role in the transmission of Legionnaires’ disease. Intracellular replication of L. pneumophila within protozoa occurs in a rough endoplasmic reticulum (RER)-surrounded phagosome (Y. Abu Kwaik, Appl. Environ. Microbiol. 62:2022–2028, 1996). Since the subsequent fate of many intracellular pathogens is determined by the route of entry, we compared the mechanisms of attachment and subsequent uptake of L. pneumophila by the two protozoa Hartmannella vermiformis and Acanthamoeba polyphaga. Our data provide biochemical and genetic evidence that the mechanisms of attachment and subsequent uptake of L. pneumophila by the two protozoan hosts are, in part, different. First, uptake of L. pneumophila by H. vermiformis is completely blocked by the monovalent sugars galactose and N-acetyl-d-galactosamine, but these sugars partially blocked A. polyphaga. Second, attachment of L. pneumophila to H. vermiformis is associated with a time-dependent and reversible tyrosine dephosphorylation of multiple host proteins. In contrast, only a slight dephosphorylation of a 170-kDa protein of A. polyphaga is detected upon infection. Third, synthesis of H. vermiformis proteins but not of A. polyphaga proteins is required for uptake of L. pneumophila. Fourth, we have identified L. pneumophila mutants that are severely defective in attachment to A. polyphaga but which exhibit minor reductions in attachment to H. vermiformis and, thus, provide a genetic basis for the difference in mechanisms of attachment to both protozoa. The data indicate a remarkable adaptation of L. pneumophila to attach and invade different protozoan hosts by different mechanisms, yet invasion is followed by a remarkably similar intracellular replication within a RER-surrounded phagosome and subsequent killing of the host cell.